Prognostic importance of expression of the Wilms’ tumor 1 gene in newly diagnosed acute promyelocytic leukemia - Hecht, Anna; Nolte, Florian; Nowak, Daniel; Nowak, Verena; Reinwald, Mark; Hanfstein, Benjamin; Weiß, Christel; Hofmann, Wolf-Karsten; Lengfelder, Eva (Leukemia and lymphoma, 2015)
Wilms’ tumor 1 gene (WT1) is known to be highly expressed in acute promyelocytic leukemia (APL) but information on its impact on prognosis is lacking. WT1 expression was analyzed in bone marrow samples of 79 patients with APL at initial diagnosis. Patients had a differing outcome according to their level of WT1 expression. In patients who achieved a complete remission (CR), low or high WT1 expression was significantly associated with inferior overall survival (OS) compared to intermediate WT1 expression (49% for WT1high vs. 63% for WT1low vs. 93% for WT1int; p = 0.008). Moreover, there were significant differences in relapse-free survival (RFS) between the three expression groups (42% for WT1high vs. 63% for WT1low vs. 83% for WT1int; p = 0.047). In multivariable analysis WT1 expression showed an independent prognostic impact on OS of responders to induction therapy. In conclusion, the level of WT1 expression can add prognostic information in APL risk stratification.